2021
DOI: 10.3390/jcm10081741
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid and T-Cell Microenvironment Immune Features Identify Two Prognostic Sub-Groups in High-Grade Gastroenteropancreatic Neuroendocrine Neoplasms

Abstract: High-grade Gastroenteropancreatic Neuroendocrine neoplasms (H-NENs) comprehend well-differentiated tumors (NET G3) and poorly differentiated carcinomas (NEC) with proliferative activity indexes as mitotic count (MC) >20 mitoses/10 HPF and Ki-67 >20%. At present, no specific therapy for H-NENs exists and the several evidences of microenvironment involvement in their pathogenesis pave the way for tailored therapies. Forty-five consecutive cases, with available information about T-cell, immune, and non-immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Our study also has limitations. A major constraint is that our nomogram was created using just six clinicopathological factors, lacking other additional variables such as Ki-67 ( 33 , 34 ), and the high Ki-67 index is associated with portal venous tumor invasion which is a prognostic factor for patients with pancreatic NENs ( 35 ). Besides, lactate dehydrogenase (LDH) has been found to increase in patients with NEC ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also has limitations. A major constraint is that our nomogram was created using just six clinicopathological factors, lacking other additional variables such as Ki-67 ( 33 , 34 ), and the high Ki-67 index is associated with portal venous tumor invasion which is a prognostic factor for patients with pancreatic NENs ( 35 ). Besides, lactate dehydrogenase (LDH) has been found to increase in patients with NEC ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a subset of NECs has microenvironment features consistent with spontaneous activation of adaptive immunity (co-expression of CD3, CD4, CD8, PD-1, and PD-L1). Recently, we further evaluated the tumor microenvironment of high-grade NENs, by expanding the immune profiling to myeloid markers and identifying two prognostic subpopulations of tumors likely compatible with the "hot/cold tumor" idea: highgrade NENs characterized by a prevalent immune infiltrate cells had better survival (67). According to this, it was suggested that microenvironment-related immune and inflammatory markers can improve prognostic prediction in GEP-NENs when combined with the known prognostic factors, and they may predict potential responsiveness to immunotherapy of GEP NECs (66,67).…”
Section: Immune Response Biomarkersmentioning
confidence: 99%
“…Recently, we further evaluated the tumor microenvironment of high-grade NENs, by expanding the immune profiling to myeloid markers and identifying two prognostic subpopulations of tumors likely compatible with the "hot/cold tumor" idea: highgrade NENs characterized by a prevalent immune infiltrate cells had better survival (67). According to this, it was suggested that microenvironment-related immune and inflammatory markers can improve prognostic prediction in GEP-NENs when combined with the known prognostic factors, and they may predict potential responsiveness to immunotherapy of GEP NECs (66,67). Furthermore, Bosch et al demonstrated that high TILs and PD-1 expression are significantly associated with shorter survival and higher grading in GEP NENs.…”
Section: Immune Response Biomarkersmentioning
confidence: 99%
“…A negative impact on the clinical course of panNET was also proposed for tumor-associated macrophages (TAM) based on their positive correlation with poor disease-specific and disease-free survival [13,14] in G1 and G2 tumors. Recent immunohistological profiling of tumor microenvironment and tumor inflammatory features pointed towards an even more prominent role of immune-related features in high grade NEN [15,16]. In a NEN cohort featuring 40% G3 specimens the authors reported a notable shift of immune tumor microenvironment (TME) marker profiles in G3 compared to G1 and G2 samples, which could be harnessed for improved stratification of the prognostic patient subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…In a NEN cohort featuring 40% G3 specimens the authors reported a notable shift of immune tumor microenvironment (TME) marker profiles in G3 compared to G1 and G2 samples, which could be harnessed for improved stratification of the prognostic patient subgroups. In a follow-up study with an extended panel of myeloid and lymphoid markers, the marker-based clustering of samples separated further prognostic subgroups within G3 NEN, with better representation of lymphoid and myeloid markers in the favorable "hot" cluster when compared to the "cold" cluster [16]. Overall, a decisive contribution of adaptive and innate immune responses in more aggressive and advanced disease situations emerges as a common theme, despite the vastly different methodological approaches and NEN cohort compositions, providing a growing rationale for immunedirected therapies.…”
Section: Introductionmentioning
confidence: 99%